Does Managerial Ownership Moderate the Value Relevance of Earnings and Equity of Sustainability Reporting? - Ihsan, Muhammad; Rexipal, Dewangga; Firmansyah, Amrie (AFEBI Management and Business Review, 2024)
This study examines the value relevance of earnings and equity of sustainability reporting through direct effect and managerial ownership as an intervening variable. This research employed quantitative data using secondary data from firms listed in IDX80, an Indonesia Stock Market index, in 2022. Also, this study used the financial elements data derived from www.idx.co.id and www.stockbit.com as complimentary. At the same time, ESG Score data were taken from www.csrhub.com. Data testing was then performed utilizing multiple linear regression analysis for cross-section data. This study concludes that sustainability reporting is positively associated with the value relevance of earnings and equity while the increases in management ownership moderate negatively to the value relevance. This study contributes to the literature on value relevance and sustainability reporting by updating the study of the value relevance of sustainability reporting both from direct influence and through managerial ownership as an intervening variable. This study is expected to suggest that the Financial Services Authority (OJK) improve financial policies in the capital market by adapting the measurement indicators in the ESG score version of CSRHUB in the POJK.